PENDIDIKAN PUSTAKAWAN BAGI MASA DEPAN PERPUSTAKAAN - Khadijah Khadijah (UIN Imam Bonjol Padang, 2019)
Abstract : Librarians need to master knowledge in the field of librarianship as a basis for carrying out their duties. It would be less effective if the librarian as manager in a library does not have knowledge in the field of librarianship. Likewise with knowledge in the field of service development, information tracking, processing and packaging of library materials, it needs to be continually sharpened by paying attention to the dynamics of information technology that is constantly changing. A librarian must have an open attitude towards renewal but not abandon the basic values of the librarians. The improvement of library development is in line with the improvement of library's positive image. If a library institution does not have a clear work plan for development, it is certain that there will be no image change in the eyes of library users. To realize this ideally, we need creative, innovative and informative librarians to package and deliver information to users in line with the development of the information world.Keyword : Education for Librarian, Librarian, InformationAbstrak : Pustakawan perlu menguasai pengetahuan di bidang kepustakawanan sebagai dasar dalam menjalankan tugasnya. Akan menjadi kurang efektif jika pustakawan sebagai manajer dalam sebuah perpustakaan tidak memiliki pengetahuan di bidang kepustakawanannya. Begitu juga dengan pengetahuan dalam bidang pengembangan pelayanan, penelusuran informasi, pengolahan dan pengemasan bahan pustaka, perlu terus diasah dengan memperhatikan dinamika teknologi informasi yang terus berubah. Seorang pustakawan harus memiliki sikap terbuka terhadap pembaharuan namun tidak meninggalkan nilai-nilai dasar kepustakawanannya. Peningkatan pengembangan perpustaakaan sejalan dengan peningkatan citra positif perpustakaan. Jika sebuah lembaga perpustakaan tidak memiliki rencana kerja yang jelas akan pengembangan, maka dapat dipastikan bahwa tidak akan ada perubahan citra di mata pengguna perpustakaan. Untuk mewujudkan hal tersebut secara ideal, diperlukan pustakawan kreatif, inovatif dan informatif dalam mengemas dan menyampaikan informasi kepada pengguna seiring dengan perkembangan dunia informasi.Kata Kunci : Perpustakaan, Pustakawan , informasi